A survey on the effectiveness of teaching languages for specific purposes at MATE - Klára, Veresné Valentinyi (Technical Languages and Translation, 2023)
In this article, a survey is presented in which we asked 11 questions about language teaching from students at the University of Agriculture and Life Sciences, MATE (528 students). The following questions were asked: How helpful was the language teacher? How up-to-date were the teaching materials? To what extent did the course material help you prepare for the professional language exam? To what extent did the course material help you to communicate in a foreign language in professional situations? To what extent did the final examination reflect the material covered in class? To what extent did the presentation in the examination reflect the material covered in class? To what extent were you prepared for each lesson? How many language classes did you miss? What would motivate you to attend and prepare for each lesson, i.e. to become a successful language learner?Overall, the students are satisfied with the content of the language lessons and the methodology and attitude of language teachers. University students want to learn specialised foreign languages related to their field of study. They emphasize the importance of oral conversation and grammar. They value teacher explanation, classroom practice and review, and regular and continuous assessments. They learn more effectively with digital tools and interactive, playful exercises. The kindness and helpfulness of the language teacher is particularly important and motivating for them, especially when it comes to students with special educational needs (SEN).  They would be more motivated if they had more language classes, if the language classes had a credit value, and if their ESP classes did not overlap with other classes.It can be concluded that the situation and problems of language learning and teaching have remained unchanged for more than two decades (Veresné Valentinyi 2011: 99–103).
Keywords: student satisfaction; teacher attitude; modern curriculum and methodology; motivation, languages for specific purposes